2016
DOI: 10.1016/j.renene.2015.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Cooling load reduction in office buildings of hot-arid climate, combining phase change materials and night purge ventilation

Abstract: a b s t r a c tNight purge ventilation is a well-known passive technique for conserving cooling energy by storing night coolth in the thermal mass of the building fabric. We study the effect of phase change materials (PCM) as a light thermal mass, on the cooling load of a typical office building with HVAC system and night purge ventilation in hot-arid climate. In this paper the proper conditions to start night ventilation and the ventilation rate by fans is determined. Additionally, the effect of melting point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…This study finds that the effectiveness of nighttime ventilation may be improved by its integration with other control methods related to occupant behavioral factors. The work of Solgi et al [38], for example, shows that integrating phase-change materials and nighttime ventilation potentially reduces the cooling load of buildings.…”
Section: Discussionmentioning
confidence: 99%
“…This study finds that the effectiveness of nighttime ventilation may be improved by its integration with other control methods related to occupant behavioral factors. The work of Solgi et al [38], for example, shows that integrating phase-change materials and nighttime ventilation potentially reduces the cooling load of buildings.…”
Section: Discussionmentioning
confidence: 99%
“…These materials have the ability to absorb and release massive amounts of energy during phase transitions with small temperature change. A lot of work has been done for thermal comfort improvement and reduction of energy consumption in buildings by integration of PCMs [2][3][4][5][6][7]. Osterman et al [8] presented a study on PCM thermal storage systems of buildings for space heating and cooling on an annual basis using 30 plates filled with paraffin.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that integrating PCMs with nighttime ventilation can achieve greater energy efficiency. Thus, PCMs are more effective in office buildings that are unoccupied during the night [38].…”
Section: Passive Building Energy Saving Technologiesmentioning
confidence: 99%